A novel long non-coding RNA Myolinc regulates myogenesis through TDP-43 and Filip1. (28th April 2018) - Militello, Giuseppe; Hosen, Mohammed Rabiul; Ponomareva, Yuliya; Gellert, Pascal; Weirick, Tyler; John, David; Hindi, Sajedah Mahmoud; Mamchaoui, Kamel; Mouly, Vincent; Döring, Claudia; Zhang, Lidan; Nakamura, Miki; et al.
Abstract: Myogenesis is a complex process required for skeletal muscle formation during embryonic development and for regeneration and growth of myofibers in adults. Accumulating evidence suggests that long non-coding RNAs (lncRNAs) play key roles in regulating cell fate decision and function in various tissues. However, the role of lncRNAs in the regulation of myogenesis remains poorly understood. In this study, we identified a novel muscle-enriched lncRNA called ' Myolinc ( AK142388 )', which we functionally characterized in the C2C12 myoblast cell line. Myolinc is predominately localized in the nucleus, and its levels increase upon induction of the differentiation. Knockdown of Myolinc impairs the expression of myogenic regulatory factors and formation of multi-nucleated myotubes in cultured myoblasts. Myolinc also regulates the expression of Filip1 in a cis -manner. Similar to Myolinc, knockdown of Filip1 inhibits myogenic differentiation. Furthermore, Myolinc binds to TAR DNA-binding protein 43 (TDP-43), a DNA/RNA-binding protein that regulates the expression of muscle genes (e.g. Acta1 and MyoD ). Knockdown of TDP-43 inhibits myogenic differentiation. We also show that Myolinc −TDP-43 interaction is essential for the binding of TDP-43 to the promoter regions of muscle marker genes. Finally, we show that silencing of Myolinc inhibits skeletal muscle regeneration in adult mice. Altogether, our study identifies a novel lncRNA that controls key regulatory networks of myogenesis.